HIPPOCRATES: A multimedia tool for distance education - Christos Bouras; Vaggelis Kapoulas; Paul Spirakis; P Lampsas; A Tatakis; D Fotakis; G Papoutsopoulos (ED-MEDIA 95, Gratz, Austria, 1995)
In this paper we present a software tool for the realisation of the distance education service, that is the conduction of classes through the use of computers. The classes are directed towards personnel in various areas and aim at the retraining and update of the personnel in subjects of special interest in their line of work. The conduction of classes takes place, from and towards, remote regions with the aid of a computer network. Hippocrates is a flexible and easy-to-use application, which permits students, who sit in front of remotely situated workstations, to attend classes or seminars given by a teacher or expert, who can also be located in some remote geographical area. Hippocrates can be thought of as a distributed transparency projector. The teacher can project transparencies on the screens of the students’ workstations and can emphasize or indicate regions of interest on them by using the graphical tools offered by Hippocrates. Immediate results of the use of Hippocrates are the fast updating of the personnel in remote areas and the upgrading of the quality of the services they offer.